Simulation and Analysis of Long-Term CO2 Trapping for the Shenhua CCS Demonstration Project in the Ordos Basin - Ying Yu; Yilian Li; Guodong Yang; Fengcheng Jiang; Sen Yang; Yongsheng Wang (Geofluids)
The Shenhua CO2 capture and sequestration (CCS) project has achieved its goal of injecting 100,000 tons/year CO2 into the saline aquifers of the Ordos Basin. This study analyzes the geochemical interactions between CO2, formation fluid, and host rock of the major formations in the Ordos Basin, assesses the CO2 trapping capabilities, and predicts the final mineral forms of injected CO2. Reactive transport simulations are performed using a 2D radial model, which represents a homogeneous formation. The results show that 80% of injected CO2 remains as free supercritical gas in each formation after injection, while most of CO2 is sequestrated in different carbonate mineral assemblages after 10,000 years. The CO2 mineral trapping capacities of the Shiqianfeng and Shihezi formations are smaller than the Liujiagou formation. Calcite, dawsonite, and siderite are stable CO2 trapping minerals, while dolomite, ankerite, and magnesite are not. The increase in porosity and permeability of the three formations in the first 100 years agrees with the observation from the Shenhua CCS Project. Also the decrease in porosity and permeability after 100 years shows agreement with other modelling studies using the similar methods. These results are useful for the evaluation of the geochemical process in long-term CO2 geological storage.